Orçamento Participativo de Porto Alegre : a emergência do clientelismo como limitador da participação social - Fontoura, Daniely Votto (2019)
Participatory democracy makes the population of a municipality active agents in various aspects of public organization, including the municipal budget. Given this, the present research presents the result of interviews conducted with members and former members of the Participatory Budgeting of Porto Alegre, thus answering the question about the emergence of the clientelist phenomenon in the process of reversal of priorities already consolidated for three decades. The method for the constitution of the corpus of this research is the semi-structured interview technique and the discourse analysis makes use of the Piagetian clinical method. The theoretical framework is distributed in the central themes Theories of Representative and Participatory Democracy and Clientelism, presenting the relations between the theoretical concepts of political-social phenomena and the speeches of the interviewees. As a result, it is demonstrated that there is space within the Representative Democracy for Social Participation and that the Porto Alegre Participatory Budget has been suffering, since 2005, a gradual loss of importance as a cornerstone of public policies and investments of the city. The clientelistic relations developed between OPPA councilors and the Municipal Administration proved to be relevant for this process of weakening the power of the community in decision making about the destinies of Porto Alegre.